Incorporation of Calcium Sulfate Dihydrate into a Mesoporous Calcium Silicate/Poly-ε-Caprolactone Scaffold to Regulate the Release of Bone Morphogenetic Protein-2 and Accelerate Bone Regeneration - Kuo-Hao Huang; Chen-Ying Wang; Cheng-Yu Chen; Tuan-Ti Hsu; Chun-Pin Lin (Biomedicines, 2021)
Tissue engineering and scaffolds play an important role in tissue regeneration by supporting cell adhesion, proliferation, and differentiation. The design of a scaffold is critical in determining its feasibility, and it is critical to note that each tissue is unique in terms of its morphology and composition. However, calcium-silicate-based scaffolds are undegradable, which severely limits their application in bone regeneration. In this study, we developed a biodegradable mesoporous calcium silicate (MS)/calcium sulfate (CS)/poly-ε-caprolactone (PCL) composite and fabricated a composite scaffold with 3D printing technologies. In addition, we were able to load bone morphogenetic protein-2 (BMP-2) into MS powder via a one-step immersion procedure. The results demonstrated that the MS/CS scaffold gradually degraded within 3 months. More importantly, the scaffold exhibited a gradual release of BMP-2 throughout the test period. The adhesion and proliferation of human dental pulp stem cells on the MS/CS/BMP-2 (MS/CS/B) scaffold were significantly greater than that on the MS/CS scaffold. It was also found that cells cultured on the MS/CS/B scaffold had significantly higher levels of alkaline phosphatase activity and angiogenic-related protein expression. The MS/CS/B scaffold promoted the growth of new blood vessels and bone regeneration within 4 weeks of implantation in rabbits with induced critical-sized femoral defects. Therefore, it is hypothesized that the 3D-printed MS/CS/B scaffold can act both as a conventional BMP-2 delivery system and as an ideal osteoinductive biomaterial for bone regeneration.